2017
DOI: 10.2741/s471
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hypoxia and TNF-alpha nbsp response by a vector with HRE and NF-kappaB response elements

Abstract: Hypoxia and inflammatory cytokine activation (H&I) are common processes in many acute and chronic diseases. Thus, a single vector that responds to both hypoxia and inflammatory cytokines, such as TNF-alpha, is useful for assesing the severity of such diseases. Adaptation to hypoxia is regulated primarily by hypoxia inducible transcription factor (HIF alpha) nuclear proteins that engage genes containing a hypoxia response element (HRE). Inflammation activates a multitude of cytokines, including TNF-alpha, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The role of Pkm2 in CM, vascular, medullary, fibrotic cells could also be diverse. Additionally, studies have shown that Pkm2 interacts with redox-inflammatory sensitive factors, such as NF-kB and Hif1a [11] possibly by direct co-factor or synergistic functions [12] in the nucleus. With increased intracellular reactive oxygen species, Pkm2, but not Pkm1, can be inhibited by cysteine-358 oxidation [13].…”
mentioning
confidence: 99%
“…The role of Pkm2 in CM, vascular, medullary, fibrotic cells could also be diverse. Additionally, studies have shown that Pkm2 interacts with redox-inflammatory sensitive factors, such as NF-kB and Hif1a [11] possibly by direct co-factor or synergistic functions [12] in the nucleus. With increased intracellular reactive oxygen species, Pkm2, but not Pkm1, can be inhibited by cysteine-358 oxidation [13].…”
mentioning
confidence: 99%